2019
DOI: 10.1080/14767058.2019.1651266
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic changes of fetal head descent at term before the onset of labor correlate with labor outcome and can be improved by ultrasound visual feedback

Abstract: Objective: The aim of the study was to evaluate the dynamic changes of angle of progression (AoP) before the onset of labor and their correlation with labor outcome and to investigate the effect of visual feedback using transperineal ultrasound on maternal pushing. Methods: We recruited a group of low-risk nulliparous women with singleton pregnancy at term. We measured AoP at rest, during pelvic floor contraction and Valsalva maneuver (before and after visual feedback). We compared AoP between women who delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
13
0
Order By: Relevance
“…An association between lower fetal head station on TPU and outcome of labor has been demonstrated in many studies. Indeed, a narrower AoP (indicating a higher fetal head station and thus less engagement) has been shown consistently to be associated with a higher risk of Cesarean delivery, longer duration of labor, failure of instrumental delivery and failure of induction of labor 15,23,34,35,45 . In the present study, we confirmed that a narrower AoP at term is associated with a higher risk of Cesarean delivery in nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…An association between lower fetal head station on TPU and outcome of labor has been demonstrated in many studies. Indeed, a narrower AoP (indicating a higher fetal head station and thus less engagement) has been shown consistently to be associated with a higher risk of Cesarean delivery, longer duration of labor, failure of instrumental delivery and failure of induction of labor 15,23,34,35,45 . In the present study, we confirmed that a narrower AoP at term is associated with a higher risk of Cesarean delivery in nulliparous women.…”
Section: Discussionmentioning
confidence: 99%
“…Antenatal pelvic floor education has been assessed. Salvesen and Mørkved 46 found that a structured pelvic floor training program was associated with a shorter second stage of labor and Youssef et al 35 . showed that visual feedback using ultrasound in nulliparous women before the onset of labor can help women push more efficiently.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, coaching and ultrasound aided visual feedback to demonstrate to women how to properly push down was found to be successful in alleviating coactivation in many cases. 86…”
Section: Assessment Of Pelvic Floor Dimensions and Functionmentioning
confidence: 99%